Analisis Hukum Unsur Pembelaan Terpaksa Atau Membela Diri Dalam Hukum Pidana - M Hafidz Faqih Alfathan; Mirza Taufiqurrahman; Azi Fernando Putra (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the elements of self-defense as regulated under Article 49 paragraph (1) of the Indonesian Penal Code (KUHP), and to evaluate the urgency of its reaffirmation in the Draft Penal Code (RKUHP). The research uses a normative and empirical juridical approach, employing literature review, court decision analysis, and interviews with legal practitioners such as defense attorneys who have handled self-defense cases, including Mr. Sukarmin, S.H. as data collection methods. Analysis of three court rulings from 2020 to 2024 reveals inconsistencies in the application of Article 49 due to the lack of clear evidentiary standards and differing judicial interpretations of proportionality in defensive actions. Furthermore, limited understanding of the defendant’s psychological state has exacerbated legal uncertainty. The current RKUHP is considered insufficiently progressive, as it largely replicates the wording of the old article without substantial improvement. From the perspective of legal practitioners, such as Mr. Sukarmin, S.H., self-defense is a legitimate right as long as it is performed in an emergency situation, without malicious intent, and does not exceed reasonable limits. He emphasized the importance of evidence and defense strategy in criminal trials, particularly the need for the accused to demonstrate that they were in a position of disadvantage—physically, numerically, or in terms of weaponry—compared to the attacker. Therefore, reaffirming the legal elements of self-defense is urgently needed to ensure legal certainty and protect citizens’ constitutional rights when facing threats. A more contextual reformulation, including recognition of noodweer excess, should be integrated into Indonesia’s criminal law reform.